Dead end in Norvelt - Gantos, Jack (Square Fish/Farrar Straus Giroux, 2013)
After being "grounded for life" by his parents, Jack Gantos is loaned out by his mother to help an old neighbor with the unusual task or writing obituaries. As Jack completes his task, he discovers the strange stories contained within the obituaries and stumbles upon what he believes may be a murder case.